PENGEMBANGAN PROFESIONALITAS GURU SEKOLAH DASAR:Studi Kasus di SD Muhammadiyah 7 Bandung - Wijayanto, Wahyu (2012)
This research aims to have perspective about planning, implementation, evaluation, supporting and resistor factors, along with efforts to cope those resistor factors of teacher professional development in elementary school. This research takes place in SD Muhammadiyah 7 Bandung. Method that used in this research is analytic descriptive with qualitative approach. Data gathering is using observation, interview, documentation study and triangulation technique. Result of this research shows that 1) planning of teacher professional development is integrated in long term school development planning and operational planning. 2) goal of teacher professional development is formulated by principal and the team which refer to school's vision and mission. 3) teacher professional development program is designed by considering quality of facilitator based on need analysis. These programs are in the form of morning assembly, apprentice, seminar, workshop, symposium, reading book, monthly routine islamic study and teacher discussion. Evaluation of teacher professional development is integrated in principal supervision which is done to find out whether or not the program success by tracking the result in student classroom learning. Supporting factors are principal leadership, teacher's motivation to learn, the existing of curriculum consultant, school infrastructure, parents and business field. Constraints factors are limitation of working time, teacher ability to learn, and funding. Efforts to cope those problems are setting Saturday as teacher learning day, stimulate teacher to achieve the best, apply individual guiding study and cooperate with stakeholders.